The Evolutions for Water Quality of Son La Hydropower Reservoir from Environmental Monitoring Data (2010 - 2018) - Xuan Duc, Do; Duc Hai, Luu; Huu Tuan, Do (VNU Journal of Science: Earth and Environmental Sciences; Vol 35 No 3DO - 10.25073/2588-1094/vnuees.4283, 2019)
In 2010, the time of blocking dams for electricity generation activities of the Son La hydropower plant on Da river, up to now, after nearly 08 years of water storage, the Son La reservoir environment has stabilized and formed the soil ecosystem. flood - typical reservoir ecosystem in the highlands of the Northwest, Vietnam. Basing on the monitoring data of the Da River at the beginning of 2010, monitoring data for Son La hydropower reservoir (2010 - 2017), monitoring data for Lai Chau hydropower reservoir (phase 1/2018). This paper uses data collection and analysis method to compare the quality of Da river water before and after the dam to the Son La reservoir at 03 observation sites: Hang Tom bridge Muong Lay, Dien Bien), Pa Uon Bridge (Quynh Nhai, Son La), Upper Muong La (Son La). Analyze the quality of Son La hydropower reservoir through input data (Lai Chau hydropower reservoir) and output at monitoring site (downstream of the dam) in Son La province during 2015-2017. The analytical results confirmed the process of changes in the groups of physical, chemical, microbiological, pesticide residues in the lake water environment and proved to change the quality of hydropower reservoirs. Son La seasonal. At the same time, discuss and evaluate some natural, social and human factors that affect the water quality of Son La hydropower reservoir.